AVAILABILITY AND EXTENT OF UTILIZATION OF TECHNOLOGICAL APPLICATIONS FOR FINANCIAL FRAUD CONTROL AND PREVENTION IN COMMERCIAL BANKS (NAU Journal of Technology and Vocational Education, 2026)
The study ascertained the availability and extent of utilization of technological applications for financial fraud control and prevention in Commercial banks in Anambra State, Nigeria. The study adopted a descriptive survey research design. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The population of the study comprised 1,092 management Staff from the 156 Commercial banks operating in Anambra State. Proportionate Stratified Random Sampling was used to select 624 respondents as sample for the study. Structured questionnaire containing 38 items was used for the study. The questionnaire was validated by three experts. The reliability of the instrument was ascertained using 20 management Staff from Commercial banks in Delta State which were not part of the population.  Reliability of the instrument was established using Cronbach Alpha’s method and the coefficient value of 0.88 was obtained. Copies of the questionnaire were administered by the researchers with the help of three research assistants. Data collected were analyzed using percentage, mean and standard deviation, while, z-test was used to test the null hypotheses. Findings of this study revealed that most of the technological applications for financial fraud control and prevention in Commercial banks were available and highly utilized, while a few were not available and some were lowly utilized. It was recommended that the management of Commercial banks should regularly review the availability and extent of utilization of technological applications to ensure adequate availability and effective utilization of technological applications for financial fraud control and prevention.
Keywords: Availability; Utilization; Technological Applications; Financial Fraud Control and Prevention; Commercial Banks